An Effort to Build Child-friendly City - Moh Ilham A Hamudy (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2015)
The research was motivated by the condition of lack attention by the local government on protecting the children and the implimentation of the issuance of Law No. 35 of 2014 on Children Protection, which mandates local governments to care the children. This study is to describe the various efforts made by the government of Surakarta and Makassar in realizing child-friendly city (KLA), the supporting and obstacle factors surrounding the KLA embodiment. By using qualitativedescriptive method, the study found some important points about the efforts of local governments on realizing the KLA. In Surakarta, for example, there have been several child-friendly community health centers (puskesmas). The Puskesmas is equipped with a private lounge complete with a childrenâ€™s playground. In addition, services for children such as nutrition garden, corner of breast milk, pediatrician, child counseling services and a child abuse victim services also continue tobe equipped. No wonder the Ministry of Women Empowerment and Child Protection Republic of Indonesia assessment scoring 713 from a total value of 31 indicators contained in the KLA who had filled the city of Surakarta. Meanwhile, Makassar City has not done a lot of local government programs, because the relatively new Makassar proclaimed KLA and is still central to reform. Among the new programs are being implemented and the Government of Makassar is giving birth certificate free of charge, to build flats in slums, and make the two villages as a KLA pilot project. The factors that affect the embodiment of the KLA is a commitment, not only commitment of the head region, but also all relevant parties. As a cross cutting issue, the KLA also requires insttersebuttional capacity, not only the capacity of Women Empowerment andChild Protection Agency as a leading sector in the KLA, but also all related other working units in the area. The success of the KLA in a city is also very depending on the commitment of all parties concerned built. In addition, the program can not be done KLA in a short time, but it needs periods of time and costly effort.Â